Designing a constellation for AIS mission based on data acquisition of LAPAN-A2 and LAPAN-A3 satellites - Mohammad Mukhayadi; Abdul Karim; Wahyudi Hasbi; Rizki Permala (Universitas Ahmad Dahlan, 2019)
Indonesia requires a maritime surveillance system that's capable to monitor its extensive waters territorial. One of the maritime standard navigation systems named AIS (Automatic Identification System), which is based on GPS and VHF digital communication, have enabled the ship monitoring in a real-time. By placing AIS receiver on the satellite, its coverage will be larger compared to the one usually placed on the seashore by maritime authority. Orbiting the AIS receiver prompted appearing the limitation of Time Division Multiple Access (TDMA) technology so the probability of ship detection would decrease drastically due to a huge number of heard ship signal simultaneously. This paper describes the design of satellite constellation for Indonesian maritime surveillance based on the result of the AIS data acquisition by LAPAN-A2 and LAPAN-A3 satellites that operate in both equatorial and polar orbit.